2021
DOI: 10.1111/jcpe.13414
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress links periodontal inflammation and renal function

Abstract: Aims Patients with chronic kidney disease (CKD) are also susceptible to periodontitis. The causal link between periodontitis and CKD may be mediated via systemic inflammation/oxidative stress. Using structural equation modelling (SEM), this cross‐sectional study aimed to explore the causal relationship between periodontal inflammation (PI) and renal function. Materials and methods Baseline data on 770 patients with stage 3–5 (pre‐dialysis) CKD from an ongoing cohort study were used. Detailed, bioclinical data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 47 publications
(65 reference statements)
0
45
0
Order By: Relevance
“…An interesting study conducted on 359 CKD patients highlighted how non-surgical periodontal treatment induced a reduction in systemic inflammation, monitored by pro-inflammatory cytokines [58]. Therefore, it is hypothesized that the treatment of CPD in CKD patients may have a positive effect on oxidative stress (OS) and on systemic inflammatory state [16,59]. These last represent prognostic factors associated with more sudden worsening of residual renal function [60].…”
Section: Periodontal Disease and Ckdmentioning
confidence: 99%
See 2 more Smart Citations
“…An interesting study conducted on 359 CKD patients highlighted how non-surgical periodontal treatment induced a reduction in systemic inflammation, monitored by pro-inflammatory cytokines [58]. Therefore, it is hypothesized that the treatment of CPD in CKD patients may have a positive effect on oxidative stress (OS) and on systemic inflammatory state [16,59]. These last represent prognostic factors associated with more sudden worsening of residual renal function [60].…”
Section: Periodontal Disease and Ckdmentioning
confidence: 99%
“…Therefore, it is plausible to hypothesize that CPD may represent an important risk factor for the onset and the progression of CKD [58]. Furthermore, the mortality rate of CKD patients seems to be profoundly increased in the presence of periodontitis [16].…”
Section: Periodontal Disease and Ckdmentioning
confidence: 99%
See 1 more Smart Citation
“…This said, these two concepts are not mutually exclusive, and therefore we must emphasize that both putative mechanisms could be involved in those associations, as demonstrated by studies that show bidirectionality of association. For instance, early epidemiological studies have demonstrated the bidirectional adverse interrelationship between an altered host inflammatory response in PD and the metabolic imbalance in diabetes (37) while more recently, a causal association was demonstrated between periodontitis and chronic kidney diseases mediated via oxidative stress (38), which seems highly relevant to this argument. We also point out that oxidative stress is a key element of PMN hyperfunctionality related to overproduction of ROS and downregulation of endogenous antioxidants such as NrF2 mediated expression of superoxide dismutase (39).…”
Section: Links Between Oral Inflammation and Systemic Diseasementioning
confidence: 99%
“…Sci. 2022, 12, 736 2 of 14 the cytokine and chemokine family, that control leucocytes and monocytes chemotaxis towards the kidney damaged site [5,6]. On the other hand, CKD is associated with a poor immune status, determined either by the diseases that cause kidney failure (for example, diabetes mellitus and cardiovascular disorders), or uremia, or as a consequence of specific therapy (dialysis or transplant).…”
Section: Introductionmentioning
confidence: 99%